DAMPAK BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA - -, Sunarso (Universitas Slamet Riyadi, 2009)
ABSTRACT Quit of leader factor and employees, communications represent important factor because partaking to support the growing of strong organization culture. With good communications will be able to be finished by existing difference between individual, superior and group Motivation have important role in supporting cultural strength of organization. For that employees require being motivated to through appreciation, attention and assist subordinate specially explain execution duty work better. Communications effectiveness does not escape with the existence of between person conflicts that go in company. Nevertheless conflict having the character of positive and in fair boundary have to be managed better. Leader in this case have to create pleasant activity relation, weaken the happening of between person conflict, and improve openness attitude and also create good cooperation. Keywords: organization cultural, leadership, motivation, communi-cations, job satisfaction.